Definition of requirements to pursue a Servitization Strategy in SME: the case of AMT firms in the Ornamental Stones cluster - Silva, J.; Simões, J. (25th EurOMA – To Serve, to Produce and to Servitize in the Era of Networks, Big Data, and Analytics, 2018)
The introduction of advanced services in a servitization business model is under close scrutiny for a SME supplying advanced technologies. The proposed conceptual model is based on three cornerstones, i.e. strategy, organizational structure, ICT requirements. It was developed and checked by using data from semi-structured interviews, unstructured observations and documentation surveying. The outcomes significance support the model usefulness within the Ornamental Stones cluster. Virtual Breeding Environments/Virtual Organizations, Digital Business Platforms, Industry4.0 and open innovation appear to be required to leverage progress towards advanced servitization and so, promote competitive advantage and cluster survival. INOVSTONE4.0 illustrates a collaborative initiative within this domain.